Solution:
Given the simultaneous equations:
![\begin{gathered} 4x+3y=15\text{ --- equation 1} \\ 5x-2y=13\text{ ---- equation 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5zlhqtmuqrwscx7htnvhffzenacljvrk0s.png)
To solve for x and y, using the elimination method, we have
![\begin{gathered} 2*(4x+3y=15)\Rightarrow8x+6y=30\text{ --- equation 3} \\ 3*(5x-2y=13)\Rightarrow15x-6y=39\text{ --- equation 4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s71vxreckgs9motctsip9dv0gr1byj8vnb.png)
Add up equations 1 and 2.
thus, this gives
![\begin{gathered} 8x+15x+6y-6y=30+39 \\ \Rightarrow23x=69 \\ divide\text{ both sides by the coefficient of x, which is 23} \\ (23x)/(23)=(69)/(23) \\ \Rightarrow x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/35yy69czjrn243i8odib0s8nw4r7w5dis9.png)
To solve for y, substitute the value of 3 for x into equation 1.
thus, from equation 1
![\begin{gathered} 4x+3y=15 \\ when\text{ x = 3,} \\ 4(3)+3y=15 \\ \Rightarrow12+3y=15 \\ add\text{ -12 to both sides,} \\ -12+12+3y=-12+15 \\ 3y=3 \\ divide\text{ both sides by the coefficient of y, which is 3} \\ (3y)/(3)=(3)/(3) \\ \Rightarrow y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zfo7p7fzh4f92m3ica7wm11vgxk1fe2cdv.png)
Hence, the solution to the equation is
![\begin{gathered} x=3 \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wkrg0wki66bvf1y7pg52ybzlfj7oys2kfd.png)